2002
DOI: 10.1038/sj.bjc.6600580
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression profiles of gastric cancer cells established from primary tumour and malignant ascites

Abstract: Advanced gastric cancer is often accompanied by metastasis to the peritoneum, resulting in a high mortality rate. Mechanisms involved in gastric cancer metastasis have not been fully clarified because metastasis involves multiple steps and requires a combination of altered expressions of many different genes. Thus, independent analysis of any single gene would be insufficient to understand all of the aspects of gastric cancer peritoneal dissemination. In this study, we performed a global analysis of the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
2
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 57 publications
2
58
2
3
Order By: Relevance
“…A 20 mg portion of total RNA extracted from each radioresistant subline was labelled with Cy3, and RNA from each parent cell line was labelled with Cy5 as described elsewhere (Sakakura et al, 2002). We used the RIKEN human cDNA microarray, which contains 21168 genes.…”
Section: Microarray Design Production and Hybridisationmentioning
confidence: 99%
See 1 more Smart Citation
“…A 20 mg portion of total RNA extracted from each radioresistant subline was labelled with Cy3, and RNA from each parent cell line was labelled with Cy5 as described elsewhere (Sakakura et al, 2002). We used the RIKEN human cDNA microarray, which contains 21168 genes.…”
Section: Microarray Design Production and Hybridisationmentioning
confidence: 99%
“…We used the RIKEN human cDNA microarray, which contains 21168 genes. Hybridisation, washing, and scanning were carried out according to a published method (Sakakura et al, 2002). These slides were scanned on a ScanArray 5000 confocal laser scanner, and the images were analysed using IMAGENE (Bio Discovery, Los Angeles, CA, USA).…”
Section: Microarray Design Production and Hybridisationmentioning
confidence: 99%
“…(13,14) Using a highdensity cDNA microarray analysis, Sakakura et al demonstrated that CD44 expression is upregulated in gastric cancer cell lines established through metastasis to the peritoneal cavity. (15) The tissue that exists between mesothelial cells and the submesothelial capillary is named the peritoneal-blood barrier, which hinders the penetration of oxygen, nutrients and drugs from the submesothelial capillary to the peritoneal cavity. (16) After the attachment of peritoneal free cancer cells on the peritoneum, most free cancer cells die off due to the existence of the peritoneal-blood barrier.…”
Section: Molecular Mechanisms Of Peritoneal Disseminationmentioning
confidence: 99%
“…These non-fluoropyrimidine nucleosides may potentially help to improve the poor prognosis observed in patients with advanced cancers involving peritoneal dissemination. (Cancer Sci 2007; 98: [11][12][13][14][15][16][17][18] P eritoneal dissemination remains the most difficult type of metastasis to treat, and almost all surgeons believe that an operation is not indicated for such metastasis.…”
mentioning
confidence: 99%
“…Integrins are composed of two different subunits, ␣ and ␤, which are noncovalently bound into ␣␤ complexes (2)(3)(4). Particularly, the expression of ␣ v ␤ 3 integrin (ABI) in tumor cells undergoing angiogenesis and on the epithelium of tumor-induced neovasculature alters the interaction of cells with the extracellular matrix, thereby increasing tumorigenicity and invasiveness of cancers (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%